MODERASI BERAGAMA: SIKAP DAN EKSPRESI PUBLIK MUTAKHIR AGAMA-AGAMA DI INDONESIA - Martin Lukito Sinaga (Jurnal Masyarakat dan Budaya, 2022)
Religious moderation is an inclusive public expression of contemporary religions, and a religious practice which is marked by respect for human dignity and aimed for a common good. It is as a timely result of a longstanding interreligious interaction in Indonesia. In this matter, therefore, religions will be better able to deal with various symptoms of social extremism and religious exclusivism. Through delving into the documents and analyzing some trainings and practices of religious moderation, it becomes increasingly clear that what is mainly to be lived out today is the virtue rooted in its own spirituality, namely moderation. In that regard, the way to train moderation, although initiated by the state office of Religious Affairs, is carried out in a reflective process into the spiritual insights of the religions themselves. It is not directed by any political interest of the state. So that subsequent expressions and religion’s public presence will reflect the indicators of religious moderation, which is tolerance, non-violence, respect for the local tradition, and the spirit of nationalism